2014
DOI: 10.1186/1471-2474-15-137
|View full text |Cite
|
Sign up to set email alerts
|

Effects of strengthening, stretching and functional training on foot function in patients with diabetic neuropathy: results of a randomized controlled trial

Abstract: BackgroundFoot musculoskeletal deficits are seldom addressed by preventive medicine despite their high prevalence in patients with diabetic polyneuropathy.AIM: To investigate the effects of strengthening, stretching, and functional training on foot rollover process during gait.MethodsA two-arm parallel-group randomized controlled trial with a blinded assessor was designed. Fifty-five patients diagnosed with diabetic polyneuropathy, 45 to 65 years-old were recruited. Exercises for foot-ankle and gait training w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
198
0
22

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 118 publications
(224 citation statements)
references
References 43 publications
4
198
0
22
Order By: Relevance
“…ABC Scale -combined (resistance/balance) exercise vs. control by the ABC Scale, there was no significant change in the groups for the study of Richardson et al 8 , but a significant improvement was shown in the intervention group for isolated activities, such as up and down stairs, activities such as standing up to pick up an object, staying on tiptoe, among others. In the analysis of the study of Sartor et al 9 , we can observe that there was significant improvement in the balance between the intervention and control groups after 12 weeks of intervention. The results suggest that after an intervention with combined exercises proposed for patients with DN, foot positioning was altered slightly, with improvement in the distribution of the dynamic pressure, in ankle extension and a better functional condition of the ankle and foot muscles.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…ABC Scale -combined (resistance/balance) exercise vs. control by the ABC Scale, there was no significant change in the groups for the study of Richardson et al 8 , but a significant improvement was shown in the intervention group for isolated activities, such as up and down stairs, activities such as standing up to pick up an object, staying on tiptoe, among others. In the analysis of the study of Sartor et al 9 , we can observe that there was significant improvement in the balance between the intervention and control groups after 12 weeks of intervention. The results suggest that after an intervention with combined exercises proposed for patients with DN, foot positioning was altered slightly, with improvement in the distribution of the dynamic pressure, in ankle extension and a better functional condition of the ankle and foot muscles.…”
Section: Discussionmentioning
confidence: 99%
“…The evidence available from the meta-analysis of these two RCTs (71 individuals), which compared exercise combined (resistance/balance) versus control, maintains that the combined exercise significantly improved the balance of individuals with DN 8,9 .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations